Facile Construction of Novel 3‑Dimensional Graphene/Amorphous Porous Carbon Hybrids with Enhanced Lithium Storage Properties - Zhu, Daming; Liu, Huaqiu; Tai, Lixuan; Zhang, Xiaonan; Jiang, Sheng; Yang, Shumin; Yi, Lin; Wen, Wen; Li, Xiaolong (ACS applied materials & interfaces, 2017)
Presently, porous materials have become essential to many technological applications. In this account, 3-dimensional skeleton composite materials consisting of a core–shell amorphous porous carbon/multilayer graphene are synthesized by chemical vapor deposition on Ni foam using a facile one-step growth method. The data suggest that these composites have not only outstanding electrical and mechanical properties of the multilayer graphene but also the mesoporous characteristics of the amorphous carbon. Moreover, the composited carbon materials perfectly inherit the macroporous structure of Ni foam, and the amorphous carbon core in the skeleton serves as a cushion to buffer the volume variation after the removal of Ni. The carbon composites reveal ultralow density (4.45 mg cm–3) and high conductivity (45 S cm–1), essentially issued from the perfectly preserved structural integrity of graphene. The novel carbon composites can be used as anodes for lithium ion batteries. After these carbon composites are incorporated with NaBiO3, superior electrochemical activities above 2 V can be achieved with a discharge capacity of ∼300 mAh g–1.